ANALISIS PENGARUH PROFITABILITAS, STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, DAN KEPEMILIKAN SAHAM MANAJERIAL TERHADAP KEBIJAKAN DIVIDEN DENGAN TARIF PAJAK SEBAGAI VARIABEL MODERASI (Studi pada Emiten yang Terdaftar di Indeks IDX High Dividend 20 Periode 2018-2021) - Novendra, Romanus Bintang Aria; Sampurno, Raden Djoko; Januard, Nana Varian (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT Dividends are one of the reasons why people buy stocks. However, different research always produce varied results when it comes to the factors that determine a company's dividend policy. The purpose of this study is to re-examine the factors that influence corporate dividend policies, particularly those of companies that consistently give substantial dividends, using changes in the dividend tax rate specified in PMK No.18 of 2021 as the moderating variable. As the object of this study, companies featured in the IDX High Dividend 20 index are used. From 2018 through 2021, 12 companies that fit the criteria were examined as samples and assessed using Moderated Regression Analysis. The research results show that profitability, capital structure, company growth and managerial share ownership are able to influence the IDX High Dividend 20 company's dividend policy, but only profitability and capital structure are able to partially influence dividend policy. The dividend tax rate has not been able to become a moderating variable, which due to the lack of reaction from investors and management in responding to these regulations. This lack of reaction is likely due to the dividend tax exemption requirements which require investors to re-invest dividends received for at least 3 years in domestic investment instruments.